Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.21608/jpp.2013.75106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Balanced Manuring by Mineral NPK and Bio-Fertilizer on Peas Productivity and Protein Content

Abstract: Two field experiments were carried out during the winter seasons of 2008/09 and 2009/10 at a private farm in Disuq district, Kafr El-Sheikh Governorate to investigate the response of pea plants, cv. Master B, to inoculation with the Rhizobium bacteria, foliar nutrition with free living bacteria (microbin) and rhizobium + N2-fixer free living bacteria compared to uninoculated with balanced monuring by NPK rates. Four levels of inorganic NPK (1-without NPK, 2-15 kg N + 25 kg P2O5 + native-K, 3-40 kg N + 30 kg P2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
(10 reference statements)
2
2
0
Order By: Relevance
“…As well the increment of pea yield and its components may be attributed to increase of plant growth characters as shown from data presented in Table 2. These results are in coincided with those obtained by Achakzai et al (2006), Dawa et al (2013), El-Waraky et al (2013), El-Sherbiny et al (2014) and Abdel Naby et al (2016).…”
Section: -Pods and Seeds Yield Componentssupporting
confidence: 92%
See 1 more Smart Citation
“…As well the increment of pea yield and its components may be attributed to increase of plant growth characters as shown from data presented in Table 2. These results are in coincided with those obtained by Achakzai et al (2006), Dawa et al (2013), El-Waraky et al (2013), El-Sherbiny et al (2014) and Abdel Naby et al (2016).…”
Section: -Pods and Seeds Yield Componentssupporting
confidence: 92%
“…As previously mentioned, both nitrogen fertilization levels and ascorbic acid concentrations (each alone) enhanced growth parameters of pea plant, thus; they together might maximize their effects leading to more yielding of pods and seeds per plant and per fed. These results are in harmony with those found by Dawa et al (2013), El-Waraky et al (2013), El-Sherbiny et al (2014 and Abdel Naby et al (2016) on pea plants. Table 4.…”
Section: -Pods and Seeds Yield Componentssupporting
confidence: 91%
“…Dawa et al (2013) indicated that increasing NPK fertilizer levels up to 100% recommended dose caused significant increases in pea plant growth (plant height, number of branches and leaves/plant and dry weight/plant) and yield and its components (pod length, number of seeds/pod, weight of 100 seeds and green pods yield/fed). El-Waraky et al (2013) revealed that increasing NPK rate up to 40 kg N + 30 kg P 2 O 5 + native-K was accompanied with significant increases in vegetative growth characters, as well as green pods yield and its components, shelling ratio, seed yield and its components, seed germination percentage, leaf contents of chlorophyll and seed content of protein. El-Sherbiny et al (2014) indicated that using of 100% mineral fertilizer gave the best value of seeds N uptake and yield as compared with either control (unfertilized, uninoculated) or other combined treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Biofertilizers may be a supplement to the organic fertilizers or it can be integrated with chemical fertilizers to reduce the cost of production and conserve soil health in vegetable plantations (El-Waraky et al, 2013). Some studies indicated that adding phosphate dissolving bacteria to chicken manure and bio-fertilizers (effective microorganism (EM) to organic fertilizer (farm yard manure) increased yield of tomato (El-Tantawy and Mohamed, 2009) and faba bean (Hellal et al, 2014), respectively, as compared to adding organic manure alone.…”
Section: Introductionmentioning
confidence: 99%